Status, distribution and local initiatives taken to conserve river dolphin, Platanista gangetica at Prakashpur-Koshi Barrage section of Koshi River (Nepal Journal of Environmental Science, 2013)
The Gangetic River Dolphin Platanista gangetica is an endangered species and this species has also been included under Appendix I of CITES. This study was based on direct count method by raft survey and multiplatform survey. In addition, questionnaire survey was also conducted with locals and fishermen of the study area to know their perceptions on dolphin. The water quality of the sites, where dolphin were seen, was analyzed using standard methods. Two dolphins were observed in the upper section of the Koshi Barrage and this is a very low number that could extinct in very future if no conservation measures are taken. Also, a rare sighting of the species has been reported by locals near irrigation canals and small tributaries of the Koshi River. Survey carried out below the Koshi Barrage revealed only four dolphins. According to local people, 10 to 15 dolphins used to appear in this section but because of change in the course by Koshi River due to the outburst of Koshi Dam, there was a low water level to support the dolphin habitat, so they might have migrated to the Ganges in India. The water quality of Koshi at the site of dolphins occurrence was determined to be normal. Accidental trapping and killing of dolphin with the use of fishing nets are identified as major threat. Various human activities like fishing, washing, transporting forest products, establishment of the ferry, construction of irrigation canals, high dams etc. ....